Mediation of calcitonin gene-related peptide in protection of ischemic preconditioning in rat hindlimbs. - Zhou Fu-Wen; Li Yuan-Jian; Deng Han-Wu (Acta Pharmacologica Sinica, 2016)
AIM: To study modulation of calcitonin gene-related peptide (CGRP) in the protective effect of ischemic preconditioning on endothelial cells. METHODS: Rat hindlmbs were subjected to ischemia for 2 h, and endothelium-dependent vasorelaxation to acetylcholine (ACh) was examined in rat hindlimbs. RESULTS: Two hours of ischemia elicited no effect on vasoconstrictor responses to norepinephrine, but markedly impaired vasodilator responses to ACh. Ischemic preconditioning induced by 5-min aortic occlusion and 10-min blood reperfusion prevented the impairment of vasorelaxation to ACh due to long-term ischemia. The protection of ischemic preconditioning was abolished by repeated pretreatments with capsaicin to deplete CGRP. Acute application of capsaicin to evoke CGRP release or CGRP caused an ischemic preconditioning-like protection. CONCLUSION: Capsaicin-sensitive sensory nerves are involved in the protective effect of ischemic preconditioning on endothelial cells in the rat hindlimbs, and CGRP can mimic the protective effect of ischemic preconditioning in blood vessels.